2019
DOI: 10.2147/cmar.s220434
|View full text |Cite|
|
Sign up to set email alerts
|

<p>LncRNA ASB16-AS1 Promotes Growth And Invasion Of Hepatocellular Carcinoma Through Regulating miR-1827/FZD4 Axis And Activating Wnt/β-Catenin Pathway</p>

Abstract: These authors contributed equally to this work Background: To date, although several long noncoding RNAs (lncRNAs) are reported to regulate hepatocellular carcinoma (HCC) development, their relationship still remains elusive. ASB16-AS1 is a poorly researched novel lncRNA. We aimed to investigate its function in HCC progression. Methods: qRT-PCR and in situ hybridization (ISH) were used to analyze ASB16-AS1 expression in HCC tissues. CCK8, Edu incorporation and colony formation were used to determine cell proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 27 publications
3
26
0
Order By: Relevance
“…In addition, upregulation of ASB16-AS1 predicted low disease-free survival rate for patients with hepatocellular carcinoma. 27 Functionally, ASB16-AS1 exerted pro-oncogenic roles in glioma 26 and hepatocellular carcinoma. 27 Nevertheless, its expression and functions in OS have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, upregulation of ASB16-AS1 predicted low disease-free survival rate for patients with hepatocellular carcinoma. 27 Functionally, ASB16-AS1 exerted pro-oncogenic roles in glioma 26 and hepatocellular carcinoma. 27 Nevertheless, its expression and functions in OS have not been thoroughly investigated.…”
Section: Discussionmentioning
confidence: 99%
“…27 Functionally, ASB16-AS1 exerted pro-oncogenic roles in glioma 26 and hepatocellular carcinoma. 27 Nevertheless, its expression and functions in OS have not been thoroughly investigated. Data from the current study revealed that ASB16-AS1 expression was increased in OS tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive evidence to date has indicated that lncRNAs can mediate the Wnt/β-catenin pathway by acting as ceRNAs of miRNAs, thereby modulating HCC cell proliferation and invasion; oncogenic lncRNAs that act as ceRNAs can perform their biological actions by activating the Wnt/β-catenin pathway in HCC. For example, frizzled (FZD) 4, a Wnt receptor, can activate the Wnt/β-catenin pathway in HCC[ 96 ], and the lncRNA ASB16-AS1 enhances FZD4 expression to activate the Wnt/β-catenin pathway by acting as a miR-1827 sponge and subsequently facilitates HCC growth and invasion[ 97 ]. Likewise, another Wnt receptor, FZD7, can also activate the Wnt/β-catenin pathway in HCC[ 98 ].…”
Section: Role Of Lncrnas As Cernas In Hccmentioning
confidence: 99%
“…Studies found that E3 ligase β-TrCP1 (BTRC) target HuR for ubiquitin-mediated protein degradation 14,16 . Several studies have found that ASB16-AS1 regulate proliferation in glioma, hepatocellular carcinoma, cervical cancer, non-small cell lung cancer, and in osteosarcoma [17][18][19][20][21] . However, whether ASB16-AS1 plays an important role in adrenocortical carcinoma remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%